Effectiveness and Safety of Highly Purified Human Menopausal Gonadotropin in Hyper Responder Iraqi Females Undergoing Intracytoplasmic Sperm Injection - Muayad Sraibet Abbood; Muhjah Falah Hassan; Saad Badai Nashtar (مجله كليه طب الكندي)
Background: The response to ovarian stimulation in females is heterogeneous, so treatment individualization offers both safety and efficacy. The use of highly purified human menopausal gonadotrophin (HP-hMG) during controlled ovarian stimulation is widely accepted nowadays but with absence of evidence demonstrating the advantages of this gonadotrophin.